Pemberdayaan Masyarakat melalui Pembentukan dan Penguatan Kelembagaan Kelompok Sadar Lingkungan sebagai Upaya Pelestarian Lingkungan di Nagari Sungai Batang - Aldri Frinaldi; Boni Saputra; Desri Nora AN; Ichsan Nasution; Yose Fajar Pratama; Adil Mubarak; Syamsir Syamsir; Asnil Asnil; Angga Putra Tri Rezeki; Irvan Renaldi (JURNAL ABDIMAS SERAWAI, 2025)
This community service program aims to empower the community of Nagari Sungai Batang, Agam Regency, by establishing and strengthening the Environmental Awareness Group (POKDARLING) to preserve the local ecosystem. This initiative involves youth and community leaders as agents of change in environmental conservation. The method employed is the Participatory Rural Appraisal (PRA) approach, which includes surveys, discussions, lectures, brainstorming sessions, and mentoring, conducted over six months (January–June 2025). The results of the activity demonstrate the establishment of a legitimate POKDARLING organizational structure through Village Head Decree No. 26 of 2025, increased community knowledge regarding environmental awareness, as well as the formation of the Youth Forum for Environmental Care and the implementation of environmental cleanup actions, all serving as tangible evidence of the program’s success. This program is expected to serve as a model for community-based environmental management that other villages in the surrounding area can adopt.